(3GdLOYs - (3LGHQ Hf MjGf Hf YHO Gddg Gdchaj, CHh ehSi, J (B200 (3g` s ((3HdOI JHQjR s)
(3ChdgG (B:s
(3bO SHb dfG bHd gPG GdcJGH KdGKI hSJhf cJGHkG ai LejY Gdafhf GdePchQI s
(3BNQgG (B:s
(3Ke Cdb Ydjg eKbGd aVI PgHoG Ydi GdNdGU agPG CUdM ddeMQbjf aGYQag s
(3Vef eLehY , JQJjHgG (B: 64s
(3YfO cQGhS GdNOYs
(3hQO cPdc ai Qbe (B96s
(3GdebGdI GdQGHYI hGdSJhf ef cJGH GdSHYjfs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdcjejGA h GdWHjYjGJs